Attenuated Vesicular Stomatitis Viruses as Vaccine Vectors - Roberts, Anjeanette (American Society for Microbiology, 1999)
We showed previously that a single intranasal vaccination of mice with a recombinant vesicular stomatitis virus (VSV) expressing an influenza virus hemagglutinin (HA) protein provided complete protection from lethal challenge with influenza virus (A. Roberts, E. Kretzschmar, A. S. Perkins, J. Forman, R. Price, L. Buonocore, Y. Kawaoka, and J. K. Rose, J. Virol. 72:4704–4711, 1998). Because some pathogenesis was associated with the vector itself, in the present study we generated new VSV vectors expressing HA which are completely attenuated for pathogenesis in the mouse model. The first vector has a truncation of the cytoplasmic domain of the VSV G protein and expresses influenza virus HA (CT1-HA). This nonpathogenic vector provides complete protection from lethal influenza virus challenge after intranasal administration. A second vector with VSV G deleted and expressing HA (ΔG-HA) is also protective and nonpathogenic and has the advantage of not inducing neutralizing antibodies to the vector itself.